ANALISIS KEPATUHAN WAJIB PAJAK ORANG PRIBADI SEBELUM DAN SESUDAH PELAKSANAAN TAX AMNESTY DI KPP PRATAMA MANADO - Pangkey, Milka Magrita; Sondakh, Jullie J.; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Tax amnesty is a government policy in the form of abolition of taxes that should be payable, not subject to tax administration sanctions and criminal sanctions in the field of taxation. Tax amnesty aims to encourage the level of public awareness and taxpayer compliance, then can increase state revenue in the field of taxation. The purpose of this research is to know the change of WPOP number after tax amnesty, and to know the level of compliance of WPOP in SPT realization and amount of SKP issued before and after tax amnesty. The object of research is KPP Pratama Manado. The analytical method used is descriptive to describe how WPOP compliance level. The results of this study indicate that the number of registered WPOP increases during the tax amnesty period. Against WPOP compliance after the amnesty tax shows, the realization of the Annual Tax Return is decreasing compared to the previous year, but the amount of SKP issued is reduced. Tax amnesty contributes 12.6% of tax revenues in 2016 in Paratama Manado's KPP.Keywords: tax amnesty, WPOP amount, WPOP compliance, tax revenue